Ephemeral Architecture as Socio-spatial Practices in Bintaro’s Modern Market Public Space - Dea Aulia Widyaevan (Institut Seni Indonesia Yogyakarta, 2022)
Ephemeral Architecture as Socio-spatial Practices in Bintaro’s Modern market Public Space. Ephemeral Architecture questions about the idea of permanence on the way we produce architecture. The term ephemeral defines as something temporary, interchangeable, and adaptive. Architecture’s vision should no longer has to be monumental or eternal, but it must be designed to became adaptive in uncertain conditions. This research offers new perspective on how architecture built from the event. The research methods, conducted in practices-based research through a series of workshop and forum group discussion in experimental architecture forum- Critical Context 3.0, 2019, conducted by LabTanya. The participants explore the notion of ephemerality on everyday design in modern market Bintaro, Jakarta by adopting phenomenology perspective in architecture. This phenomenology perspective transcribes in a way a phenomenon observes in term of body, gestures, movement in relation to time and social consent produced these momentarily space. The modern market (as a case study) gives context on how this place are became a melting point of several functions, time and places. This research finds that there are several strategies on how the tenant are inhabiting the space in performative and temporals way to resolve the spatial limitations. Arsitektur Efemera sebagai Praktek Ruang Sosial Pada Ruang Publik Pasar Modern Bintaro. Arsitektur Efemera, mempertanyakan tentang gagasan keabadian dalam cara mendesain arsitektur. Istilah efemera atau sesaat, didefinisikan sebagai sesuatu yang sementara, selalu mengalami transformasi, dan adaptif. Visi arsitektur tidak lagi harus monumental atau abadi, tetapi harus dirancang untuk menjadi adaptif dalam kondisi konteks lingkungan yang dinamis. Penelitian ini menawarkan perspektif baru tentang bagaimana arsitektur dibangun dari sebuah peristiwa. Metode penelitian, berbasis praktik melalui serangkaian lokakarya dan forum diskusi yang digagas pada forum arsitektur eksperimental- Critical Context 3.0, 2019, oleh LabTanya, Jakarta. Para peserta mengeksplorasi gagasan arsitektur efemera/sesaat pada desain keseharian di pasar modern Bintaro, Jakarta melalui perspektif fenomenologi. Perspektif ini, menginvestigasi bagaimana tubuh, gerak dan waktu selalu berkaitan dengan konteks sosial suatu tempat. Pasar modern (sebagai studi kasus) memberikan konteks bagaimana tempat ini merupakan titik lebur dari beberapa fungsi, kaya akan ruang-ruang sementara (spatio temporal). Hasil penelitian ini menemukan beberapa strategi ruang adaptif, yang dilakukan oleh para penyewa pasar, dalam mengatasi keterbatasan ruang.